A method for determining the content of cross-linked lignin in lignocellulose

By carboxymethylation and acid hydrolysis ashing treatment of lignocellulose, combined with ultraviolet-visible spectroscopy detection, the problem that the existing technology cannot detect crosslinked lignin content is solved, and crosslinked lignin in lignocellulose is achieved Accurate determination and analysis of content.

CN115236020BActive Publication Date: 2024-12-17INST OF BIOLOGICAL & MEDICAL ENG GUANGDONG ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210868192.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-22
Publication Date
2024-12-17
Estimated Expiration
2042-07-22

AI Technical Summary

Technical Problem

Existing methods cannot effectively detect and analyze the content of crosslinked lignin in lignocellulose.

Method used

Carboxymethylated lignocellulose was formed by reacting lignocellulose powder with compounds such as isopropanol, sodium hydroxide and monochloroacetic acid, and then the absorbance of non-crosslinked and crosslinked lignin was detected using an ultraviolet-visible spectrometer, combined with Acid hydrolysis and ashing steps to calculate the acid-soluble and acid-insoluble crosslinked lignin content.

Benefits of technology

It realizes accurate detection of the crosslinked lignin content in lignocellulose, with a wide range of application, a small sample volume, and accurate measurement results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003759360760000061
    Figure BDA0003759360760000061
  • Figure BDA0003759360760000071
    Figure BDA0003759360760000071
Patent Text Reader

Abstract

The invention discloses a method for determining the content of cross-linked lignin in lignocellulose. The lignocellulose is dried and ground into fine powder; the lignocellulose powder is weighed and put into a beaker, isopropanol is added, and stirred to obtain a uniform suspension; sodium hydroxide solution is added to the suspension and stirred evenly; monochloroacetic acid is added, stirred to react, and a yellow carboxymethylated lignocellulose solid suspension is obtained; acetic acid is dripped to adjust the pH of the suspension to neutral, and then the suspension is filtered and the solid is collected; the solid is dissolved again in a methanol solution, the suspension is filtered, and the solid is collected; then pure methanol is used to rinse the solid twice, and the solid is placed in freeze drying to obtain pure carboxymethylated lignocellulose. The invention can detect and analyze the content of cross-linked lignin in lignocellulose. The invention has accurate measurement results and a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmentally friendly new energy production, and specifically relates to a method for determining the content of cross-linked lignin in lignocellulose. Background Art

[0002] Lignocellulose is a renewable resource widely found in nature, mainly composed of cellulose, hemicellulose and lignin. Lignin accounts for about 15-30%, and is a natural polymer compound composed of phenylpropane structural units connected by ether bonds and carbon-carbon bonds. Lignin and cellulose or hemicellulose molecules are mainly bound by hydrogen bonds and covalent bonds. As one of the three major components of lignocellulose, the content and structure of lignin are key factors affecting its properties, application methods, and processing technology. Therefore, the determination of lignin content is a very important link.

[0003] The quantitative methods of lignin can be summarized into two categories: direct determination and indirect determination. The direct determination methods can be divided into two types according to the existence form of lignin: residue (solid) form and dissolved form. The methods for determining the lignin content in the form of residue are Klason method and acid lithium bromide method. Both methods are to dissolve the carbohydrates in lignocellulose, polymerize lignin molecules into insolubles, precipitate lignin in the form of residue, and then measure its mass to calculate the lignin content. The indirect methods for determining the lignin content are spectroscopy and redox method. Spectroscopy is to detect the lignin content by means of infrared, ultraviolet and nuclear magnetic resonance spectra. The methods for determining the lignin content by ultraviolet are acetyl bromide method and thioglycolic acid method. These two methods use the principle that the concentration of dissolved lignin is linearly correlated with ultraviolet absorption for determination. The redox method is based on the fact that the reaction rate of the oxidant with lignin is much higher than the reaction rate of carbohydrates, so that the consumption of the oxidant in the prescribed procedure is used as a standard for measuring the lignin content. Although the above methods can determine the lignin content, each method has its advantages and disadvantages, and its determination method is constantly being improved. Currently there is no method to detect and analyze the content of cross-linked lignin in lignocellulose. Summary of the invention

[0004] The purpose of the present invention is to provide a method for determining the content of cross-linked lignin in lignocellulose. The present invention has the characteristics of requiring a small amount of sample, a wide range of application, and accurate determination results.

[0005] The method for determining the content of cross-linked lignin in lignocellulose provided by the present invention comprises the following steps:

[0006] (1) Dry the wood cellulose and grind it into fine powder.

[0007] (2) Weigh the lignocellulose powder into a beaker, add isopropanol, and stir to obtain a uniform suspension;

[0008] (3) adding sodium hydroxide solution to the suspension and stirring evenly;

[0009] (4) adding monochloroacetic acid and stirring to react to obtain a yellow carboxymethylated lignocellulose solid suspension;

[0010] (5) adding acetic acid dropwise to adjust the pH of the suspension to neutral, then filtering the suspension and collecting the solid;

[0011] (6) dissolving the solid again in a methanol solution (e.g., a methanol solution with a volume fraction of 80%), filtering the suspension, and collecting the solid; then washing the solid twice with pure methanol, and placing the solid in a freeze-dryer to obtain pure carboxymethylated lignocellulose;

[0012] (7) placing the carboxymethylated lignocellulose obtained in step (6) into a beaker, adding purified water, and stirring to obtain a yellow uniform syrup;

[0013] (8) The syrup is centrifuged and then filtered to separate, and the filter residue is repeatedly washed with acetone, the filtrate is a lignocellulose solution without cross-linked lignin, and the filter residue is a lignocellulose solid containing cross-linked lignin.

[0014] (9) After the filtrate is suspended and evaporated to a solid, it is redissolved in pure water and the volume is fixed to 10 mL; the absorbance of the filtrate at a wavelength of 240-320 nm is detected by a UV-visible spectrometer, and the non-cross-linked lignin content M1 is calculated according to the formula:

[0015] Calculation formula for non-crosslinked lignin content M1 (%):

[0016] Wherein, m is the mass of lignocellulose powder, g; UV abs is the absorbance of the raw material at an appropriate wavelength; V is the volume of the solution to be measured, L; ε is the absorbance of the raw material at a specific wavelength; L is the optical path length of the ultraviolet visible light in the measuring instrument, cm.

[0017] (10) Take the filter residue obtained in step (8), add 72% sulfuric acid at a ratio of 1 g / 10 mL, hydrolyze at 30° C. for 1 h, then dilute the acid to 4%, and then hydrolyze at 121° C. for 1 h, filter the hydrolyzate to obtain a filtrate and a solid residue. Use an ultraviolet-visible spectrometer to detect the absorbance of the filtrate at a wavelength of 240-320 nm. abs , the acid-soluble cross-linked lignin content M2 is calculated according to the formula; the solid residue is placed in a crucible, dried at 105°C to constant weight, and then incinerated at 600°C to calculate the acid-insoluble cross-linked lignin content M3:

[0018] Calculation formula for acid-insoluble cross-linked lignin content M2 (%):

[0019] Calculation formula for acid-soluble cross-linked lignin content M3 (%):

[0020] Wherein, m is the mass of lignocellulose powder, g; m1 is the total weight of crucible and solid residue, g; m2 is the total weight of crucible and ash after calcination at 600℃, g; UV abs is the absorbance of the raw material at an appropriate wavelength; V is the volume of the solution to be measured, L; ε is the absorbance of the raw material at a specific wavelength; L is the optical path length of the ultraviolet visible light in the measuring instrument, cm.

[0021] Preferably, the particle size of the lignocellulose powder in step (1) is 20-80 mesh.

[0022] Preferably, the ratio of the lignocellulose powder to isopropanol in step (2) is 1 g / 10 mL to 1 g / 100 mL.

[0023] Preferably, the concentration of sodium hydroxide in step (3) is 5-9M.

[0024] Preferably, the ratio of the lignocellulose powder to the sodium hydroxide in step (3) is 1 g / 1 mL to 1 g / 10 mL.

[0025] Preferably, the mass ratio of the lignocellulose powder to monochloroacetic acid in step (4) is 1:0.5 to 1:3.

[0026] Preferably, the amount of methanol used in step (6) is such that the ratio of lignocellulose powder to methanol solution is 1 g / 50 mL to 1 g / 500 mL.

[0027] Preferably, the mass fraction of the methanol solution in step (6) is 60-90%.

[0028] Compared with the existing technology, the present invention has the following advantages:

[0029] The invention can detect and analyze the content of cross-linked lignin in lignocellulose, and has accurate measurement results and a wide range of applications. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the embodiments.

[0031] In order to better understand the present invention, the following embodiments of the present invention are used to further illustrate the content of the present invention, but the content of the present invention is not limited thereto.

[0032] Embodiment 1:

[0033] (1) Dry the bagasse and grind it through a 20-80 mesh sieve. 10 g of bagasse powder was weighed and put into a beaker, 100 mL of isopropanol was added, and the mixture was stirred for 5 to 10 minutes to obtain a uniform suspension; 10 mL of a 7.5 M sodium hydroxide solution was added to the suspension with a dropper, and then the mixture was stirred with a rotor for 10 minutes; 5 g of monochloroacetic acid was added, and then the mixture was stirred with a rotor in a water bath at 55° C. for 3 hours to obtain a yellow carboxymethylated bagasse solid suspension; acetic acid was added dropwise to adjust the pH of the suspension to neutral, and then the suspension was filtered and the solid was collected; the solid was dissolved again in 500 mL of a methanol solution with a volume fraction of 80%, the suspension was filtered, and the solid was collected; then the solid was rinsed twice with pure methanol, and the solid was freeze-dried for 12 hours to obtain pure carboxymethylated bagasse; the carboxymethylated bagasse was put into a beaker, pure water was added, and yellow uniform syrup was obtained after stirring; the syrup was centrifuged at high speed for 5 minutes, and then filtered and separated, and the filter residue was repeatedly rinsed with acetone, the filtrate was bagasse without cross-linked lignin, and the filter residue was bagasse containing cross-linked lignin. After the filtrate is suspended and evaporated to a solid, it is redissolved in pure water and fixed to 10 mL; the absorbance of the filtrate at a wavelength of 240 nm is detected by a UV-visible spectrometer, and the non-cross-linked lignin content M1 is calculated according to the formula. Sulfuric acid with a mass fraction of 72% is added to the filter residue at a ratio of 1 g / 10 mL, and concentrated acid is hydrolyzed at 30°C for 1 hour, then the acid is diluted to 4%, and hydrolyzed at 121°C for 1 hour, and the hydrolyzate is filtered to obtain a filtrate and a solid residue. The absorbance of the filtrate at a wavelength of 240 nm is detected by a UV-visible spectrometer, and the acid-soluble cross-linked lignin content M2 is calculated according to the formula; the solid residue is placed in a crucible, dried at 105°C to constant weight, and then ashed at 600°C to calculate the acid-insoluble cross-linked lignin content M3.

[0034] Embodiment 2:

[0035] (1) Dry the corn cobs and grind them through a 20-80 mesh sieve. Weigh 10g corn cob powder and put it into a beaker, add 1000mL of isopropanol, stir for 5-10min to obtain a uniform suspension; add 100mL of 9M sodium hydroxide solution to the suspension with a dropper, and then stir for 10min; add 30g of monochloroacetic acid, and then stir in a 55°C water bath for 3h to obtain a yellow carboxymethylated corn cob solid suspension; drop acetic acid to adjust the pH of the suspension to neutral, then filter the suspension and collect the solid; dissolve the solid again in 5000mL of 60% methanol solution by volume, filter the suspension and collect the solid; then rinse the solid twice with pure methanol, freeze-dry the solid for 12h to obtain pure carboxymethylated corn cob; put the carboxymethylated corn cob into a beaker, add pure water, and stir to obtain a yellow uniform syrup; centrifuge the syrup at high speed for 5min, then filter and separate, and repeatedly rinse the filter residue with acetone, the filtrate is corn cob without cross-linked lignin, and the filter residue is corn cob containing cross-linked lignin. After the filtrate is suspended and evaporated to solid, it is redissolved in pure water and fixed to 10mL; the absorbance of the filtrate at a wavelength of 320nm is detected by UV-visible spectrometer, and the non-cross-linked lignin content M1 is calculated according to the formula. Sulfuric acid with a mass fraction of 72% is added to the filter residue at a ratio of 1g / 10mL, and concentrated acid is hydrolyzed at 30℃ for 1h, then the acid is diluted to 4%, and hydrolyzed at 121℃ for 1h, and the hydrolyzate is filtered to obtain a filtrate and a solid residue. The absorbance of the filtrate at a wavelength of 320nm is detected by UV-visible spectrometer, and the acid-soluble cross-linked lignin content M2 is calculated according to the formula; the solid residue is placed in a crucible, dried at 105℃ to constant weight, and then ashed at 600℃ to calculate the acid-insoluble cross-linked lignin content M3.

[0036] Embodiment 3:

[0037] The reed stems are dried and crushed through a 20-80 mesh sieve. 10 g of reed stem powder is weighed and put into a beaker, 500 mL of isopropanol is added, and the mixture is stirred for 5 to 10 minutes to obtain a uniform suspension; 50 mL of a sodium hydroxide solution with a concentration of 7.5 M is added to the suspension, and the mixture is then stirred with a rotor for 10 minutes; 15 g of monochloroacetic acid is added, and the mixture is then stirred with a rotor in a water bath at 55° C. for 3 hours to obtain a yellow carboxymethylated reed stem solid suspension; acetic acid is dripped into the suspension to adjust the pH value of the suspension to neutral, and the suspension is then filtered and the solid is collected; the solid is again dissolved in 2000 mL of a methanol solution with a volume fraction of 90%, the suspension is filtered, and the solid is collected; the solid is then rinsed twice with pure methanol, and the solid is placed in a freeze-drying machine for 12 hours to obtain pure carboxymethylated reed stem; the carboxymethylated reed stem is placed in a beaker, pure water is added, and the mixture is stirred to obtain a yellow uniform syrup; the syrup is centrifuged at high speed for 5 minutes, and then filtered and separated, and the filter residue is repeatedly rinsed with acetone, wherein the filtrate is reed stem without cross-linked lignin, and the filter residue is reed stem containing cross-linked lignin. After the filtrate is suspended and evaporated to a solid, it is redissolved in pure water and fixed to 10 mL; the absorbance of the filtrate at a wavelength of 240 nm is detected by a UV-visible spectrometer, and the non-cross-linked lignin content M1 is calculated according to the formula. Sulfuric acid with a mass fraction of 72% is added to the filter residue at a ratio of 1 g / 10 mL, and concentrated acid is hydrolyzed at 30°C for 1 hour, then the acid is diluted to 4%, and hydrolyzed at 121°C for 1 hour, and the hydrolyzate is filtered to obtain a filtrate and a solid residue. The absorbance of the filtrate at a wavelength of 240 nm is detected by a UV-visible spectrometer, and the acid-soluble cross-linked lignin content M2 is calculated according to the formula; the solid residue is placed in a crucible, dried at 105°C to constant weight, and then ashed at 600°C to calculate the acid-insoluble cross-linked lignin content M3.

[0038] Embodiment 4:

[0039] Comparative study on different methods for quantification of various lignocelluloses

[0040]

[0041]

[0042] Although the embodiments of the present invention are described above, the present invention is not limited to the above specific embodiments and application fields, and the above specific embodiments are only illustrative and instructive, but not restrictive. Under the guidance of this specification, a person skilled in the art can make many forms without departing from the scope of protection of the claims of the present invention, which all belong to the protection of the present invention.

Claims

1. A method for determining the content of cross-linked lignin in lignocellulose, characterized in that It’s quick and easy and consists of the following steps: (1) Drying the wood cellulose and grinding it into fine powder; (2) Weigh the lignocellulose powder into a beaker, add isopropanol, and stir to obtain a uniform suspension; (3) Add sodium hydroxide solution to the suspension and stir evenly; (4) adding monochloroacetic acid and stirring to react to obtain a yellow carboxymethylated lignocellulose solid suspension; (5) adding acetic acid dropwise to adjust the pH of the suspension to neutral, then filtering the suspension and collecting the solid; (6) Dissolving the solid again in a methanol solution, filtering the suspension, and collecting the solid; then washing the solid twice with pure methanol, and freeze-drying the solid to obtain pure carboxymethylated lignocellulose; (7) placing the carboxymethylated lignocellulose obtained in step (6) into a beaker, adding purified water, and stirring to obtain a yellow uniform syrup; (8) centrifuging the syrup, filtering and separating it, and repeatedly washing the filter residue with acetone, wherein the filtrate is a lignocellulose solution without cross-linked lignin, and the filter residue is a lignocellulose solid containing cross-linked lignin; (9) After the filtrate is suspended and evaporated to a solid, it is redissolved in pure water and the volume is fixed to 10 mL; the absorbance of the filtrate at a wavelength of 240-320 nm is detected by a UV-visible spectrometer, and the non-cross-linked lignin content M1 is calculated according to the formula: Calculation formula for non-cross-linked lignin content M1 (%): Where, m is the mass of lignocellulose powder, g; UV abs is the absorbance of the raw material at an appropriate wavelength; V is the volume of the solution being measured, L; ε is the absorbance of the raw material at a specific wavelength; L is the optical path length of the ultraviolet visible light in the measuring instrument, cm; (10) Take the filter residue obtained in step (8), add 72% sulfuric acid at a ratio of 1 g / 10 mL, hydrolyze at 30°C for 1 h, then dilute the acid to 4%, and then hydrolyze at 121°C for 1 h, filter the hydrolyzate to obtain a filtrate and a solid residue; use a UV-visible spectrometer to detect the absorbance of the filtrate at a wavelength of 240-320 nm. abs , the acid-soluble cross-linked lignin content M2 is calculated according to the formula; the solid residue is placed in a crucible, dried at 105°C to constant weight, and then incinerated at 600°C to calculate the acid-insoluble cross-linked lignin content M3: Calculation formula of acid-insoluble cross-linked lignin content M2 (%): Calculation formula for acid-soluble cross-linked lignin content M3 (%): Wherein, m is the mass of lignocellulose powder, g; m1 is the total weight of crucible and solid residue, g; m2 is the total weight of crucible and ash after calcination at 600°C, g; UV abs is the absorbance of the raw material at an appropriate wavelength; V is the volume of the solution to be measured, L; ε is the absorbance of the raw material at a specific wavelength; L is the optical path length of the ultraviolet visible light in the measuring instrument, cm.

2. The method according to claim 1, characterized in that: The particle size of the lignocellulose powder in step (1) is 20-80 mesh.

3. The method according to claim 1, characterized in that The ratio of the lignocellulose powder to isopropanol in the step (2) is 1 g / 10 mL to 1 g / 100 mL.

4. The method according to claim 1, characterized in that: The concentration of sodium hydroxide in step (3) is 5-9M.

5. The method according to claim 4, characterized in that The ratio of the lignocellulose powder to the sodium hydroxide in the step (3) is 1 g / 1 mL to 1 g / 10 mL.

6. The method according to claim 1, characterized in that The mass ratio of the lignocellulose powder to monochloroacetic acid in step (4) is 1:0.5 to 1:

3.

7. The method according to claim 1, characterized in that The amount of methanol solution used in step (6) is 1 g / 50 mL to 1 g / 500 mL in a ratio of lignocellulose powder to methanol solution.

8. The method according to claim 1, characterized in that The methanol solution is a methanol solution with a volume fraction of 80%.

9. The method according to claim 1, characterized in that: The mass fraction of the methanol solution in step (6) is 60-90%.